If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + 2Yb = 14 Solving 3X + 2bY = 14 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2bY' to each side of the equation. 3X + 2bY + -2bY = 14 + -2bY Combine like terms: 2bY + -2bY = 0 3X + 0 = 14 + -2bY 3X = 14 + -2bY Divide each side by '3'. X = 4.666666667 + -0.6666666667bY Simplifying X = 4.666666667 + -0.6666666667bY
| -2x+5/3=7/8 | | k^2+5k+6=(k+2)(k+12) | | 2+4i=-4x+12yi | | k^2+5k+6=(k+2)(k+6) | | -4-4v-9+-6v= | | 9y+4=8y+1 | | k^2+5k+6=(k+2)(k+3) | | -8+w=15 | | .05x+.06y=58 | | 3/4=6/z | | 1/a=5/30 | | x^2-y^2+8x-2y-21=0 | | -4c+-10c-4c+8c= | | 32=7x-1+2x | | (15x^8/y^7)(3x^8y^7/7) | | 1-7f=-3f+10 | | 6b+27=-4-3 | | 750+22n(n-12)=650+30(n-10) | | 4(X+1)(x-1)= | | 3x+x-5=3x+6 | | 7x^2+23x-4=0 | | (5x-9)-1=(4-3x)(-2)+10 | | 750+22n(n-12)=650+30n(n-10) | | 6+3y-1=5y+14-3y | | 65x=1300 | | 12x^2+7=-12x | | 8+2+8c= | | -4/5(n-6)=12 | | 20=1/5w | | c+cx=b-bx | | (9i)(2i)= | | 0=y-14-2y |